Immunoaffinity Purification of HTC Rat Hepatoma Cell Plasminogen Activator-Inhibitor-1 - Zeheb, Ron; Rafferty, Usha M; Rodriguez, Miguel A; Andreasen, Peter; Gelehrter, Thomas D (Thrombosis and Haemostasis, 1987)
Incubation of HTC rat hepatoma cells with the synthetic glucocorticoid dexamethasone rapidly inhibits tissue-type plasminogen activator activity by inducing a specific plasminogen activator-inhibitor (PAI-1). Using immobilized polyclonal antibodies raised against HT-1080 human fibrosarcoma PAI-1, we have purified HTC PAI-1 from serum-free medium conditioned by dexamethasone-treated HTC hepatoma cells and shown it to be antigenically related to human PAI-1. Greater than 100-fold purification with greater than 75% yield was achieved in a single step. The purified PAI-1 migrates on SDS-polyacrylamide gels as a single major band of 49 kDa with a minor band of 46 kDa. Digestion of PAI-1 with endoglycosidase F causes a shift toward faster migrating species which retain inhibitory activity. The purified PAI-1 was stable at pH 2.5, lost 50% of its activity after 15 min at 45° C, and showed marked activation after treatment with SDS or guanidine-HCl. Purified PAI-1 rapidly inhibited and formed complexes with both tissue-type and urokinase-type plasminogen activators. Polyclonal rabbit antirat PAI-1 antibodies were raised which immunoprecipitate both free and complexed PAI-1.
Keywords: Plasminogen activator-inhibitor; HTC rat hepatoma cells; Purification; Antibody